Preparation and characterization of edible carboxymethyl cellulose films containing natural antibacterial agents: Lysozyme. (15th August 2022) - Hu, Xiaoxian; Liu, Yaofa; Zhu, Dandan; Jin, Yongguo; Jin, Haobo; Sheng, Long
Highlights: CMC and lysozyme were successfully employed to produce novel antibacterial films. CMC-Lys films were more water-resistant than pure CMC films. CMC-Lys films had better mechanical properties than pure CMC films. CMC-Lys films had antibacterial properties in application experiment. Molecular changes between CMC and lysozyme were confirmed. Abstract: Carboxymethyl cellulose (CMC) films containing lysozyme (Lys) were prepared in this study and changes in properties of the films were investigated. Enhancement in mechanical properties was observed with increased Lys, maximum (0.05 g/100 mL) reached to 39.07 MPa (TS) and 25.04 % (EAB). Meanwhile, water resistance ability improved, the minimum (0.05 g/100 mL) reached to 0.42 g·mm·(m 2 ·h·KPa) -1, 84.62 % of pure CMC film. Thermogravimetric test showed better thermal stability of films. Scanning electron microscope illustrated that few cracks on surface of films. Fourier Transform infrared spectroscopy supported that more intermolecular hydrogen between Lys and CMC was formed with increased Lys, yet keeping increasing formed less intermolecular hydrogen. X-ray Diffraction observed the aggregated Lys by crystal structure. Antibacterial test showed an inhibitory effect on two common food-borne pathogens. Weight loss experiment indicated that films reduced the dry consumption of meat. Overall, the modification of CMC film by adding Lys was effective.